Career Planning Profile of Vocational School Students in Bogor Regency: Comprehensive Perspective and Strategic Role of Career Guidance - Silvia Agustina; Mamat Supriatna; Eka Sakti Yudha (Universitas PGRI Yogyakarta, 2026)
This study analyzes the career-planning profiles of Vocational High School students in Bogor Regency, an area with a growing industry but high unemployment among Vocational High School graduates. Using a quantitative descriptive survey, data were collected from 506 tenth-grade tourism students. A 46-item instrument was validated using the Rasch Model in Winstep software version 5.7.3, chosen for its detailed item fit analysis and for ensuring measurement reliability with ordinal data. Results showed that 72.13% of students were in the